Synthesis of Transition Metal Diethyldithiocarbamates and Their Effect on Nodulation and Other Growth Characters in Mungbean, Vigna radiata - ARORA, ANUPMA; ARORA, C.L. (Asian Journal of Chemistry, 2010)
The present investigation involves the synthesis of some metal diethyldilbiocarbamates and their effect on symbiotic activity of mungbean. Metal diethyldithiocamates, [(C2H5)2NCS2]nM (M = Zn, Mn, Cd), were synthesized by the reaction of metal chloride with sodium diethyldithiocarbamate in dichloromethane/water mixture. The metaI-complexes were soluble in chloroform, carbon tetrachloride, telrahydrofuran and benzene. The dithiocarbamate ligand acted as bidentate in all the metal-complexes. The metaI-complexes were screened for theit effect on growth characters and symbiotic activity of mungbean, Vigna radiata ML 267 at various concentrations. The complexes of zinc and manganese significantly increased the dry weight of root and shoot, number of nodules, dry, weight of nodules and chlorophyll content of leaves.